Where NGOs go and do not go? - Mallick, Debdulal; Nabin, Munirul H. (BRAC, 2019)
We aim to investigate the role of output market imperfections in constraining the microfinance programme to mitigate credit market imperfections. We develop a model in which output market imperfections increase operating costs for nongovernment organizations (NGO) and create barriers for producers to market their goods. Therefore, NGOs operate in locations having good physical infrastructure and better productive. and marketing opportunities to minimize operating costs and maximize loan repayment. Using data from northern Bangladesh, we found strong support for the model predictions. NGO coverage in a village, measured both by percentage of NGO member households and number of NGOs working, decreased with distance of the village from marketplace and increased with adoption of modern irrigation method and soil quality. NGOs did not consider poverty incidence in the village. The results have important implications for development economics in general and impact assessment of microfinance programme in particular.